(NpROBLEMY FIZI^ESKOJ ORGANI^ESKOJ HIMII (B:s ((NsTROENIE(B, (NSPEKTRALXNO(B-(NL@MINESCENTNYE I FOTOHIMI^ESKIE SWOJSTWA NENASY]ENNYH KETONOW I (B2-(NPIRAZOLINOW(B) /s - (NmITINA(B, (NwALENTINA gEORGIEWNAs; (NkUTULQ(B, (NlIDIQ aNTONOWNAs; (NsUHORUKOW(B, (NaNDREJ aLEKSANDROWI^s; (NlAWRU[IN(B, (Nw(B.(Nf(B.s ((NhARXKOW (B:s (NiZD(B-(NWO hARXKOWSKOGO GOS(B. (NUN(B-(NTA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 144-151 (141 (NNAZW(B.)s
Keywords: (NkETONY NEPREDELXNYEs; (NpIRAZOLINs; (NfOTOHIMIQs